2000
DOI: 10.1034/j.1600-0749.2000.130308.x
|View full text |Cite
|
Sign up to set email alerts
|

Depigmenting Effects of Calcium d‐Pantetheine‐S‐Sulfonate on Human Melanocytes

Abstract: The effects of calcium D-pantetheine-S-sulfonate (PaSSO3Ca) on human pigmentation were examined by in vitro assays using two types of human melanocytes: normal adult melanocytes (HNM) and M4Be melanoma cells. The compound, when added to a culture medium at doses indicating no cytotoxicity, causes a visually recognizable, reversible loss of pigment in both types of cells. Determination of melanin content, incorporation of 14C-DOPA into melanins and tyrosinase activities demonstrated that treatment of these cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…This study demonstrated that piperlonguminine could downregulate α ‐MSH‐induced tyrosinase expression at the transcription level via a decrease of CREB phosphorylation, which is a rare mechanism for depigmenting efficacy. Several depigmenting agents have been also reported with diverse mechanisms of interference on melanin synthesis and deposition; arbutin and kojic acid targeting for tyrosinase activity (Kahn, 1995; Maeda and Fukuda, 1996), α ‐linolenic acid for tyrosinase degradation (Ando et al., 1998), RWJ‐50353 for protease‐activated receptor 2‐mediated melanosome transfer (Seiberg et al., 2000), and calcium D‐pantetheine‐S‐sulfonate for tyrosinase glycosylation (Franchi et al., 2000).…”
Section: Discussionmentioning
confidence: 99%
“…This study demonstrated that piperlonguminine could downregulate α ‐MSH‐induced tyrosinase expression at the transcription level via a decrease of CREB phosphorylation, which is a rare mechanism for depigmenting efficacy. Several depigmenting agents have been also reported with diverse mechanisms of interference on melanin synthesis and deposition; arbutin and kojic acid targeting for tyrosinase activity (Kahn, 1995; Maeda and Fukuda, 1996), α ‐linolenic acid for tyrosinase degradation (Ando et al., 1998), RWJ‐50353 for protease‐activated receptor 2‐mediated melanosome transfer (Seiberg et al., 2000), and calcium D‐pantetheine‐S‐sulfonate for tyrosinase glycosylation (Franchi et al., 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Glucosamine or tunicamycin, specific inhibitors of lipid carrier‐dependent glycosylation of protein, have been found to induce, in melanoma cells, a marked loss of pigmentation associated with ultrastructural alterations of melanogenic compartments (19). Calcium d ‐pantetheine‐ S‐sulphonate (PaSSO 3 Ca), probably through the alteration of tyrosinase and TRP‐1 glycosylation, causes an inhibition of melanogenic enzymes, without modifying their expression, and produces a reversible loss of pigmentation in normal human melanocytes and in melanoma cell lines (20).…”
Section: Glycosylation and Maturation Of Melanogenic Enzymesmentioning
confidence: 99%
“…In a distinct study by Choi et al , treatment of HM3KO melanoma cells with deoxynojirimycin, a α-glucosidase inhibitor that disrupts early ER N -glycan processing, and deoxymannojirimycin, an inhibitor of α-1,2-mannosidase which are thought to be responsible for late glycan processing, showed inhibition of glycosylation, transportation of tyrosinase to the melanosome and melanin synthesis [42]. Other factors explored for their ability to modulate tyrosinase glycosylation include calcium d -pantetheine- S -sulfonate [43], ferritin [44] and glutathione [45]. Glutathione induced inhibition of tyrosinase glycosylation, blocks the maturation and transfer of tyrosinase from GERL (Golgi-endoplasmic reticulum-lysosome)-coated vesicles to the pre-melanosome.…”
Section: Post-translational Modification Of Melanogenic Enzymesmentioning
confidence: 99%